Egalitarianisme Muslim Dan Nonmuslim Dalam Kitab Al-Musāwah Al-Insāniyyah Karya ‘Ali Jum’ah - Falah, Muhammad Fajrul (Syariah: Journal of Fiqh Studies, 2023)
The relationship between non-Muslims and their status in the Muslim community, according to Islamic law, it is a topic that has been discussed for a long time. The development of human civilization brought about the ideas of Muslim and non-Muslim egalitarianism. However, in the classical jurisprudence literature, non-Muslims have always been positioned as second-class people in Muslim societies. One of the modern ulama who contributed to this discourse is 'Ali Jum'ah. His capacity as someone who has served as Grand Mufti in Egypt makes his thoughts urgent to study. For this reason, this study aims to analyze the thoughts of 'Ali Jum about Muslim and non-Muslim egalitarianism in his book Al-Musāwāh Al-Insāniyyah Fī Al-Islām Bayna An-Na ariyyah wa At-Taṭbīq. To achieve these objectives, the method used in this research is content analysis, which is classified as a qualitative method that uses descriptive analytics. As a result, 'Ali Jum'ah's thoughts on Muslim and non-Muslim egalitarianism in that book have an aqliy and naqliy basis, and contain four main principles; justice (al-‘adālah), tolerance (at-tasāmuḥ), brotherhood (al-ukhuwwah), and freedom (al-ḥurriyah). Meanwhile, its scope covers only the rights and obligations of a human nature. In the book, 'Ali Jum’ also provides several forms of contextualization of Muslim and non-Muslim egalitarianism. Some of the ideas of 'Ali Jum'ah in the book also confront the fiqh theories written by the majority of Shafi’i madhab fuqahā.’ Thus, some of his ideas contradict these theorie.